Squamous Cell Carcinoma Arising from Remnant of Mullerian Duct With 47XYY Karyotype – Rare Case - Padmanabhan, Anitha; Kadam, Ashvini Dhondiram; Gadgil, Nitin (Annals of Pathology and Laboratory Medicine, 2022)
Persistent Mullerian duct syndrome (PMDS) is a rare type of male pseudohermaphroditism characterized by the presence of Mullerian derivatives (uterus, fallopian tubes and upper vagina), cryptorchidism either unilateral or bilateral along with inguinal hernia in a phenotypically and genotypically male person. PMDS is rarely associated with malignancies, the most common being testicular germ cell tumours. Occasional case of Adenocarcinoma arising in the PMD remnant structure is reported. We report an unusual case of male type of PMDS with squamous cell carcinoma (SCC) arising from PMD derivatives and presented with hematuria Also, this patient had karyotype of 47XYY (Jacob syndrome). Both these are hitherto unreported in English literature to the best of our knowledge.